2017
DOI: 10.1111/ssm.12231
|View full text |Cite
|
Sign up to set email alerts
|

How Picture Books on the National Science Teacher's Association Recommend List Portray Scientists

Abstract: This study utilized the Draw‐A‐Scientist Test Checklist (DAST‐C) to assess the illustrations of scientists in the most recent three years of NSTA Recommends book lists. A total of 15,778 images were contained in the 148 books from those lists, of which 1,676 were of scientists. ANOVA procedures revealed no significant differences in stereotypical elements across the three years of books. However, three notable stereotypical elements were present in large percentages in books from all years: predominance of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Overall, the results in the present study suggest that the current format of the DAST‐C appears as a generally appropriate measure of perceptions of scientists. Certain prevalent stereotypes of scientists found in this analysis are consistent with the previous literature: Students still view scientists as middle‐aged Caucasian men who wear white lab coats and work in a laboratory (Barman, ; Farland‐Smith, ; Farland‐Smith et al, ; Mead & Métraux, ). This study also supports the previous research that found a low prevalence of certain stereotypes in students’ drawings, such as Mythic Stereotypes, Indications of Danger, Indications of Secrecy, and Presence of Light Bulbs (Finson, ; Thomas & Hairston, ; Türkmen, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, the results in the present study suggest that the current format of the DAST‐C appears as a generally appropriate measure of perceptions of scientists. Certain prevalent stereotypes of scientists found in this analysis are consistent with the previous literature: Students still view scientists as middle‐aged Caucasian men who wear white lab coats and work in a laboratory (Barman, ; Farland‐Smith, ; Farland‐Smith et al, ; Mead & Métraux, ). This study also supports the previous research that found a low prevalence of certain stereotypes in students’ drawings, such as Mythic Stereotypes, Indications of Danger, Indications of Secrecy, and Presence of Light Bulbs (Finson, ; Thomas & Hairston, ; Türkmen, ).…”
Section: Discussionsupporting
confidence: 89%
“…The DAST‐C was also used to access the images of scientists contained in 56 books on the National Science Teachers Association recommended list. Using the DAST‐C, findings indicate that images most frequently depicted middle‐aged or elderly Caucasian male scientists, but other stereotypical components also appeared with some frequency such as eyeglasses and facial hair (Farland‐Smith, Finson, & Arquette, ). This points to an ongoing need to ensure that the science community, from teachers to textbook publishers, is aware of implicit biases in science education and stereotypes that persist about scientists.…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted, Finson (2002) noted the stereotypical perceptions of a scientist, and how this can affect students' subject selection. Farland-Smith et al (2017) found similar, whilst analysing images in books, with a particular focus on the depiction of scientists. They note that in 2015 and 2016 over 70% of images in these books were male, which may add to children's perceptions of a scientist's identity (Farland-Smith et al, 2017).…”
Section: Influences On Stereotypical Gender Beliefsmentioning
confidence: 69%
“…A recent study [18] examined the visual representations of scientists in NSTA's Outstanding Trade Books Awardees from 2014 to 2016. Results revealed that many of the books, more than half did not include any visual representations of scientists, and those that did signiicantly reinforced the misconception that scientists are males who are Caucasian.…”
Section: Scientists In Trade Booksmentioning
confidence: 99%